A personalized biomimetic dual-drug delivery system via controlled release of PTH1-34 and simvastatin for in situ osteoporotic bone regeneration - Xu, Tongtong; Gao, Shang; Yang, Nan; Zhao, Qi; Zhang, Yutong; Li, Tieshu; Liu, Zhihui; Han, Bing (Frontiers in Bioengineering and Biotechnology, 2024)
Patients with osteoporosis often encounter clinical challenges of poor healing after bone transplantation due to their diminished bone formation capacity. The use of bone substitutes containing bioactive factors that increase the number and differentiation of osteoblasts is a strategy to improve poor bone healing. In this study, we developed an in situ dual-drug delivery system containing the bone growth factors PTH1-34 and simvastatin to increase the number and differentiation of osteoblasts for osteoporotic bone regeneration. Our system exhibited ideal physical properties similar to those of natural bone and allowed for customizations in shape through a 3D-printed scaffold and GelMA. The composite system regulated the sustained release of PTH1-34 and simvastatin, and exhibited good biocompatibility. Cell studies revealed that the composite system reduced osteoblast death, and promoted expression of osteoblast differentiation markers. Additionally, by radiographic analysis and histological observation, the dual-drug composite system demonstrated promising bone regeneration outcomes in an osteoporotic skull defect model. In summary, this composite delivery system, comprising dual-drug administration, holds considerable potential for bone repair and may serve as a safe and efficacious therapeutic approach for addressing bone defects in patients with osteoporosis.